Role of Alphasatellite in Begomoviral Disease Complex: Begomoviral Disease and Alphasatellite - Shahid, Muhammad Shafiq; Ilyas, Mehmoona; Waheed, Abdul; Gaur, Rajarshi Kumar (Biological Sciences - PJSIR, 2016)
A circular single stranded satellite, called as alphasatellite (initially identified as DNA-1), was characterised and confirmed to be associated with the Geminivirus begomovirus-betasatellite complexes. Alphasatellites are single stranded DNA (ssDNA) components, frequently accompanying with monopartite begomovirus or some time with bipartite begomovirus and/or betasatellite complex. The genome of alphasatellite DNAs are nearly half size of its helper virus genome and have no similarity with it. Furthermore, their function in begomovirus-betasatellite complex is still unclear. Recent advances in application of molecular tools helped in finding new viruses and allied satellite components that further help in advancing our understanding o f this satellite DNA and this evolution